Elements of an index-based margin insurance: An application to wheat production in Austria - Karin Heinschink; Franz Sinabell; Thomas Url (Austrian Institute of Economic Research (WIFO), 2017)
Farmers may use financial market instruments to hedge price risks. Moreover, various types of insurance products are on the market to protect against production losses. An insurance that covers losses of both input and output prices was recently introduced in the USA. We develop this concept further by proposing a prototype of an index-based margin insurance which accounts for both production risks and price risks (input and output prices). The prototype is based on standardised gross margin time series for specific activities. It accounts for revenues, variable costs by cost item, various insurance coverage levels, and gross margin. Indemnities are paid if the gross margin falls short of a determined level. We identify steps necessary to accomplish a market-ready insurance product (e.g., data validation, defining the details of the sub-indexes and the premium calculation, evaluating acceptance on the market prior to its launch). Using Austrian data, the innovative approach is exemplified with respect to different farm management practices, more specifically for the case of conventional and organic wheat production. Farmers could benefit from such a margin insurance since production and price risks would be covered in one scheme, thus reducing opportunity costs.
Keywords: G22; G32; Q12; Q14; Q18; 330; natural hazards; price risk; margin insurance